MicroRNA Profiling: From Dark Matter to White Matter, or Identifying New Players in Neurobiology - Anna M. Krichevsky (The Scientific World Journal)
Contemporary biology has been revolutionized by a recently discovered class of small regulatory RNA molecules, microRNAs (miRNAs). Missed by researchers for decades due to their tiny size, usually mapping to non-protein-coding regions of genomes, miRNAs and miRNA-mediated regulatory networks have been the “dark matter” of molecular biology. Deciphering miRNA pathways and functions in the CNS of complex organisms is tightly linked to understanding miRNA expression patterns. To facilitate these emerging studies, I here review the basic principles of medium- and high-throughput technologies available for miRNA expression profiling.